2007
DOI: 10.1186/1471-2350-8-28
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of N-acetyltransferase 1 and 2 polymorphisms and haplotype analysis for inflammatory bowel disease and sporadic colorectal carcinoma

Abstract: BackgroundN-acetyltransferase 1 (NAT1) and 2 (NAT2) are polymorphic isoenzymes responsible for the metabolism of numerous drugs and carcinogens. Acetylation catalyzed by NAT1 and NAT2 are important in metabolic activation of arylamines to electrophilic intermediates that initiate carcinogenesis. Inflammatory bowel diseases (IBD) consist of Crohn's disease (CD) and ulcerative colitis (UC), both are associated with increased colorectal cancer (CRC) risk. We hypothesized that NAT1 and/or NAT2 polymorphisms contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…and either UC or CD. The NAT2 slow frequency was approximately 55% in all groups of UC, CD and healthy controls, which is in agreement with another Caucasian study [28]. A study of a Japanese population showed an association between the NAT2*7B slow acetylator haplotype and CD, but no association was found between all NAT2 slow acetylator phenotypes and CD or UC [22].…”
Section: Prevalence Of Polymorphismssupporting
confidence: 52%
“…and either UC or CD. The NAT2 slow frequency was approximately 55% in all groups of UC, CD and healthy controls, which is in agreement with another Caucasian study [28]. A study of a Japanese population showed an association between the NAT2*7B slow acetylator haplotype and CD, but no association was found between all NAT2 slow acetylator phenotypes and CD or UC [22].…”
Section: Prevalence Of Polymorphismssupporting
confidence: 52%
“…Patients with IBD have a higher risk of colorectal cancer than general population and are predisposed to this complication. This risk is related to the extent and duration of disease, but not disease activity [29,37,38]. The risk of malignant transformation is particularly high for patients having the disease for longer than 8 years for patients with UC affecting the entire colon.…”
Section: Discussionmentioning
confidence: 95%
“…The present results suggested that CYP2D6*1 allele and EM genotype may be involved in risk of inflammatory bowel disease. Mahid et al [38] reported that the continuous state of inflammation and repair in IBD may increase both the frequency and propagation of genetic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Ricart et al [41] reported 54.7% of rapid acetylators among 64 UC patients treated with sulphasalazine, a proportion similar to that found in the American population. A Chinese study [42] did not disclose any relationship of NAT2 genotype with susceptibility of IBD (mainly UC), neither did Mahid et al [43] in a study that included 167 UC, 201 CD patients and 223 controls. Two of these studies [41,43] also identified the NAT1 genotype, without finding any difference with controls.…”
Section: Inflammatory Bowel Disease (Ibd)mentioning
confidence: 90%